Exploring Students’ Awareness of Research Methodology: The Case of Second Year Master Students of English at Frères Mentouri University, Constantine1, Algeria - Semakdji, Fatima-Zohra (Journal of Human Sciences, 2022)
From our experience as a teacher and supervisor at the Department of Letters and English, Frères Mentouri University, we have observed a general dissatisfaction on the part of teachers with second year Master students’ inability to write a Master dissertation that conforms to the requirements of research methodology. Through this paper, we set out to explore students’ awareness of the fundamentals of research methodology, particularly research topic selection, statement of the problem, research aims, extended literature survey, research questions, hypothesis formulation, means of research, data collection, analysis of results and ethics of research. A descriptive quantitative study has been carried out using a teachers’ questionnaire as a tool for collecting data. Results have demonstrated that there is remarkable lack of awareness on the part of students of the aforementioned fundamentals of research methodology, as evidenced by most of the teachers’ responses.